Republished: Developing capable quality improvement leaders. Issue 1048 (21st January 2013) - Kaminski, Geraldine M; Britto, Maria T; Schoettker, Pamela J; Farber, Stacey L; Muething, Stephen; Kotagal, Uma R
Abstract : Background/objective: Cincinnati Children's Hospital Medical Center created the Intermediate Improvement Science Series (I 2 S 2 ) training course to develop organisational leaders to do improvement, lead improvement and get results on specific projects. Design methods: Each multidisciplinary class consists of 25–30 participants and 12 in-class training days over 6 months. Instructional methods include lectures, case studies, interactive application exercises and dialogue, participant reports and assigned readings. Participants demonstrate competence in improvement science by completing a project with improvement in outcome and/or process measures. They present on their projects and receive feedback during each session and one-on-one coaching between sessions. Results: Since 2006, 279 participants in 11 classes have completed the I 2 S 2 course. Participant evaluations have consistently rated satisfaction, learning, application, impact and value very high. Large and statistically significant changes were observed in pre-course to post-course self-assessment of knowledge of five quality improvement topics. Approximately 85% of the projects demonstrated measurable improvement. At follow-up, 72% of improvement projects were completed and made a part of everyday operations in the participant's unit or were the focus of continuing improvement work. Many changes were spread to other units or programmes. Most (88%) responding graduates continued to participate in formal quality improvement efforts and many led other improvement projects. Nearly half of the respondents presented their results at one or more professional conference. Conclusions: Through the I 2 S 2 course, the authors are developing improvement leaders, accelerating the shift in the culture from a traditional academic medical centre to an improvement-focused culture, and building cross-silo relationships by developing leaders who understand the organisation as a large system of interdependent subsystems focused on improving health.